Urban Renewal, Community and Participation Theory, Policy and Practice (The Urban Book Series,, 2018)
This edited collection investigates the human dimension of urban renewal, using a range of case studies from Africa, Asia, Europe, India and North America, to explore how the conception and delivery of regeneration initiatives can strengthen or undermine local communities. Ultimately aiming to understand how urban residents can successfully influence or manage change in their own communities, contributing authors interrogate the complex relationships between policy, planning, economic development, governance systems, history and urban morphology. Alongside more conventional methods, analytical approaches include built form analysis, participant observation, photographic analysis and urban labs. Appealing to upper level undergraduate and masters' students, academics and others involved in urban renewal, the book offers a rich combination of theoretical insight and empirical analysis, contributing to literature on gentrification, the right to the city, and community participation in neighbourhood change. .